Motivation and Arabic learning achievement: a comparative study between two types of Islamic schools in Gansu, China - Qiao, JuPing; Abu Kassim, Noor Lide; Badrasawi, Kamal J I (Springer Heidelberg, 2013)
The Self-determination theory (SDT) developed by Ryan and Deci (1985), has been applied by many L2 researchers to explicate the relationship between motivation and L2 learning outcomes from social and psychological perspectives. In addition, SDT distinguishes intrinsic motivation from extrinsic motivation on L2 learning achievement. Bakar et al. (J Lang Stud, 10(1):71–86, 2010) in their study extended Ryan and Deci’s self-determination theory to investigate the role of religious motivation in Arabic (L2) language learning achievement. This study sought to extend previous findings by examining the relationship between motivation aspects: Religious Motivation (RM), Internal Motivation (IM), External Motivation (EM), and Amotivation (AM) and Arabic language learning achievement. Specifically, it aims to (a) explore factors that influence Arabic learning achievement and examine the relative contribution of the different aspects of motivation (RM, IM, EM and AM) on Arabic language learning achievement; (b) investigate the relationship between those aspects; and (c) compare the level of motivation across two subgroups of Arabic language learners. To achieve these purposes, 348 students were randomly selected from two types of Gansu Islamic schools in China to complete a 36-item questionnaire.